2021
DOI: 10.6007/ijarbss/v11-i16/11232
|View full text |Cite
|
Sign up to set email alerts
|

Family Traditional Bakery Business Sustainability: An Analysis on its Contributing Success Factors

Abstract: The waves of civilization, industrialization, technological innovations, economic growth and increasing welfare of people have undoubtedly altered or changed the traditional food culture, including the traditional food products. Some might argue that the traditional foods products are slightly over ruined by the modern foods that seem to be more attractive and trendier. Whether this connotation holds true is not known. This paper attempted to identify the factors that affect the continuation of the family trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This section discusses the related literature. Misran et al (2021) explored the sustainable management factors of traditional family bakeries, and the research used ethnographic technique with seven days of continuous observation, and finally a narrative method to illustrate the research findings, the results show that five key factors can affect the sustainable operation of the bakery, including products, equipment, materials, customers and knowledge transfer. Martínez-Monzó et al (2013) identified fundamental trends in bread, baking and pastry innovations related to health, happiness and convenience requirements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This section discusses the related literature. Misran et al (2021) explored the sustainable management factors of traditional family bakeries, and the research used ethnographic technique with seven days of continuous observation, and finally a narrative method to illustrate the research findings, the results show that five key factors can affect the sustainable operation of the bakery, including products, equipment, materials, customers and knowledge transfer. Martínez-Monzó et al (2013) identified fundamental trends in bread, baking and pastry innovations related to health, happiness and convenience requirements.…”
Section: Literature Reviewmentioning
confidence: 99%